Enantioselective Synthesis of Polycyclic Nitrogen Heterocycles by Rh-Catalyzed Alkene Hydroacylation: Constructing Six-Membered Rings in the Absence of Chelation Assistance - Du, Xiang-Wei (American Chemical Society, 2014)
[Image: see text] Catalytic, enantioselective hydroacylations of N-allylindole-2-carboxaldehydes and N-allylpyrrole-2-carboxaldehydes are reported. In contrast to many alkene hydroacylations that form six-membered rings, these annulative processes occur in the absence of ancillary functionality to stabilize the acylrhodium(III) hydride intermediate. The intramolecular hydroacylation reactions generate 7,8-dihydropyrido[1,2-a]indol-9(6H)ones and 6,7-dihydroindolizin-8(5H)-ones in moderate to high yields with excellent enantioselectivities.